Pusat Perawatan Dan Pendidikan Kecantikan di Kota Makassar - Reski Amalia; Andi Muhammad Akbar; Usman Fahruddin (Universitas Muslim Indonesia, 2023)
In the era of rapid beauty industry development, the importance of appearance has made skincare and beauty treatments a primary focus for both men and women. The beauty industry in Indonesia, particularly in Makassar City, has experienced significant growth. This research proposes the concept of a centralized Beauty Care and Education Center to address challenges and support economic growth while meeting the needs of the Makassar community. The research method employed is qualitative, involving data collection from various sources, both primary and secondary. Secondary data is obtained through literature reviews, while preliminary data is gathered through direct observations of the Beauty Care Center building. The analysis results indicate that the site location was chosen considering ideal sun exposure, facing south, to maximize morning sunlight utilization. Additionally, using a second skin is being considered to reduce afternoon sun heat. The building's design is based on the Metaphor concept, drawing inspiration from snails and chamomile flowers, often used in skincare products. The structural and construction system involves: The use of pile foundations, Reinforced concrete for column structures, A hollow steel roof frame. The lighting and ventilation systems combine natural and artificial lighting, while utilities involve electricity sourced from the national grid and backup generators, as well as a clean water supply and wastewater disposal system.